A new approach to intensity and load monitoring and its potential use in training, games, and recovery in handball. Could it become a useful tool? - Hatzimanouil, Dimitris S.; Skandalis, Vasilis G.; Stavropoulou, Georgia N.; Lola, Afroditi C.; Giannakoulakos, Stavros A. (Zdorov'i︠a︡, sport, reabilitat︠s︡ii︠a, 2025)
Background and purpose Athletes’ monitoring is a critical issue in the high-performance sporting environment. The CR-10 RPE scale has become a standard method to evaluate perceived exertion in exercise testing, training, and rehabilitation. Handball training should be measurable, but there is not just one indicator or methodology to be applied to the different training types that this sport requires. Although there is great access to technology, a need for alternative monitoring in handball using a tool which is cheap, practical and user friendly is necessary and essential. The aim of this present research was first to correlate Borg’s Rate of Perceived Exertion (RPE) monitoring method, with Foster’s exercise score, creating a new interpretation, the Exertion Intensity Scale (EIS) and second to find if there is an effect of fatigue and training intensity of the players on the attendance to the physiotherapist for different types of recovery. Material and Methods The sample of the research consisted of 18 high level Women Handball players and coaching staff, who evaluated the intensity of the training and the sensation of fatigue and also the training components and the main subject of each training accordingly. Descriptive and inductive statistics were used for the statistical analysis. Results From the comparison of the two scales (RPE & EIS), it appears that there was a strong correlation between them. Furthermore, it is confirmed that, as the intensity of training increases so does the fatigue of the players. It also seems in the case of intensity of training and games, there was a statistically significant effect on visits to the physiotherapist for active recovery. Conclusions From the results we can conclude that the Exertion Intensity Scale (EIS) and Rating of Perceived Exertion (RPE) scales can be used as everyday tools for load and intensity monitoring in handball. Обоснование и цель Мониторинг спортсменов является критически важным вопросом в спортивной среде высоких достижений. Шкала RPE CR-10 стала стандартным методом оценки воспринимаемой нагрузки при тестировании с физической нагрузкой, тренировках и реабилитации. Тренировки по гандболу должны быть измеримыми, но не существует какого-то одного показателя или методологии, применимой к различным типам тренировок, необходимых для этого вида спорта. Несмотря на широкий доступ к технологиям, потребность в альтернативном мониторинге в гандболе с использованием дешевого, практичного и удобного для пользователя инструмента является необходимой и существенной. Целью настоящего исследования было, во-первых, сопоставить метод мониторинга скорости воспринимаемого напряжения (RPE) Борга с оценкой упражнений Фостера, создав новую интерпретацию, шкалу интенсивности напряжения (EIS), а во-вторых, выяснить, существует ли эффект усталости и интенсивность подготовки игроков к посещению физиотерапевта при различных видах восстановления. Материал и методы Выборку исследования составили 18 женщин-гандболисток высокого уровня и тренерский состав, которые оценивали интенсивность тренировки и ощущение усталости, а также компоненты тренировки и основной предмет каждой тренировки соответственно. Для статистического анализа использовались описательная и индуктивная статистика. Результаты Сравнение двух шкал (RPE и EIS) показывает, что между ними существует сильная корреляция. Более того, подтверждено, что с увеличением интенсивности тренировок растет и утомляемость игроков. Также кажется, что в случае интенсивности тренировок и игр наблюдался статистически значимый эффект от посещения физиотерапевта для активного восстановления. Выводы По результатам можно сделать вывод, что шкала интенсивности нагрузки (EIS) и шкала оценки воспринимаемой нагрузки (RPE) могут использоваться в качестве повседневных инструментов для мониторинга нагрузки и интенсивности в гандболе. Обгрунтування і мета Моніторинг спортсменів є критичним питанням у спортивному середовищі високої продуктивності. Шкала CR-10 RPE стала стандартним методом оцінки відчутного навантаження під час тестування фізичних навантажень, тренувань і реабілітації. Тренування гандболу має бути вимірюваним, але не існує лише одного показника чи методології, які слід застосовувати до різних типів тренувань, необхідних для цього виду спорту. Незважаючи на широкий доступ до технологій, потреба в альтернативному моніторингу в гандболі за допомогою інструменту, який є дешевим, практичним і зручним для користувача, є необхідною та важливою. Мета цього нинішнього дослідження полягала, по-перше, у співвіднесенні методу моніторингу швидкості сприйнятого навантаження (RPE) Борга з оцінкою фізичних навантажень Фостера, створивши нову інтерпретацію, Шкалу інтенсивності навантаження (EIS), а по-друге, виявити, чи є вплив втоми та інтенсивність тренувань гравців щодо відвідування фізіотерапевта для різних видів відновлення. Матеріал і методи Вибірка дослідження складалася з 18 гандболісток високого рівня та тренерського складу, які оцінювали інтенсивність тренування та відчуття втоми, а також тренувальні компоненти та основну тему кожного тренування відповідно. Для статистичного аналізу використовували описову та індуктивну статистику. Результати З порівняння двох шкал (RPE та EIS) виявляється, що між ними існує сильна кореляція. Крім того, підтверджено, що зі збільшенням інтенсивності тренувань зростає і втома гравців. Також видається, що у випадку інтенсивності тренувань та ігор спостерігався статистично значущий вплив на візити до фізіотерапевта для активного відновлення. Висновки З результатів ми можемо зробити висновок, що шкали інтенсивності навантаження (EIS) і оцінки сприйнятого навантаження (RPE) можна використовувати як щоденні інструменти для моніторингу навантаження та інтенсивності в гандболі.